2011
DOI: 10.1080/09603107.2011.587770
|View full text |Cite
|
Sign up to set email alerts
|

Small sample properties of copula-GARCH modelling: a Monte Carlo study

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…It is well-known, since the work by Fiorentini et al (1996), that the estimation of GARCH models is complex and requires large samples. Moreover, the large simulation studies of GARCH processes in Hwang and Valls Pereira (2006), Fantazzini (2009) and Bianchi et al (2011) showed that a sample of at least 250-500 observations is needed to have good model estimates and, in case of complex data-generating processes, even larger samples are required.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known, since the work by Fiorentini et al (1996), that the estimation of GARCH models is complex and requires large samples. Moreover, the large simulation studies of GARCH processes in Hwang and Valls Pereira (2006), Fantazzini (2009) and Bianchi et al (2011) showed that a sample of at least 250-500 observations is needed to have good model estimates and, in case of complex data-generating processes, even larger samples are required.…”
Section: Resultsmentioning
confidence: 99%
“…The seminal work by Fiorentini et al (1996) highlighted the issues involved in GARCH model estimation, emphasizing the demand for large datasets. Furthermore, comprehensive simulation studies conducted by Hwang and Valls Pereira (2006), Fantazzini (2009), andBianchi et al (2011) underscored the requirement of a sample size ranging from 250 to 500 observations for obtaining reliable model estimates of basic GARCH models. For scenarios involving more complex data generating processes, even larger sample sizes were necessary to ensure robust estimation.…”
Section: Benchmark Volatility Models For Daily Datamentioning
confidence: 99%
“…Nesse tamanho amostral o viés das estimativas de todos os parâmetrosé próximo a zero. Esses resultados estendem as evidências de simulação identificadas por Bianchi et al (2011), que no entanto, analisam o modelo Cópula GARCH para o caso em que os choques aleatórios seguem a distribuição t-Student. Além disso, percebeu-se que em dados com maior curtose excedente os estimadores apresentam melhores propriedades.…”
Section: Avaliação Dos Estimadores Pontuaisunclassified
“…A estimação dos parâmetros do modeloé baseada no método de máxima verossimilhança. Como relatado ao longo do trabalho esses estimadores podem conduzir a resultados inferenciais distorcidos em pequenas amostras (Hwang & Pereira, 2006, Xie, 2009, Bianchi et al, 2011. Nesse sentido, esse trabalho analisou por meio de simulações de Monte Carlo as propriedades dos estimadores do modelo Beta-Skew-t-EGARCH em amostras de tamanho finito.…”
Section: Considerações Finaisunclassified
See 1 more Smart Citation